(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
Abstract The purpose of this study is to explain and describe the microstructural aspects of Sri Setyorahayu’s "White Letter" geguritan (hereinafter abbreviated as GSP). The approach through the microstructural aspect sees that discourse is formed in two aspects, namely in terms of the relationship of form and the relationship of meaning. This type of research is descriptive qualitative. The data source is the GSP contained in the book “Tembang dan Puisi Jawa Modern” by Prof. Dr. Herman J. Waluyo, M.Pd., et al. 2012, page 49. The research data is GSP text. Data is collected by read and record method. Data analysis techniques use two methods, namely the distribution method and the matching method. The agih method examines the cohesion and linguistic structure of discourse, while the equivalent method is used to examine context. Research data validation uses data triangulation. After the data is analyzed, it is then interpreted and classified according to the research objectives and makes conclusions. The results and conclusions of the research state that the microstructural aspects of GSP consist of both grammatical and lexical cohesion. Grammatical cohesion consists of references, substitutions, elepsis, and conjunctions; while lexical cohesion consists of repetition, synonymy, collocation, and equivalence.